Design and Structural Characteristics Analysis of Fast Docking for the Fairing - ZHANG Yuan; FAN Hua-ping; JIANG Xiao-han; LI Xi-han (Journal of Harbin University of Science and Technology)
Based on the characteristics of fairing structure docking, in order to shorten the time required for docking, a locking claw form fairing butt joint structure has been designed. Compared with the existing fairing bolt connection, the new connection structure of the fairing can drive the connecting locking hook through the gear rack, effectively improve the fairing docking speed. Threedimensional model of the connection structure has been established based on the new fairing connection structure, applying ANSYS Workbench finite element analysis software, the single fairing connection structure analysis of structural characteristics. The results show that: compared with structure with existing fairing connection, the new fast connection can not only meet the environmental vibration during payload launching and docking speed requirements, but also reduce the docking time by 74%.